Analisis Pengembangan Sumber Daya Manusia Dalam Perspektif Syariah - Anisatul Maghfiroh (ITB AAS INDONESIA Surakarta, 2021)
Human Resources is something that is very influential for the progress of an institution. Without quality human resources, an institution will not develop and may even experience setbacks. Therefore, every organization must prepare a program that contains activities that can increase the capabilities and professionalism of human resources so that the organization can survive and develop in accordance with the organizational environment. This program is usually referred to as human resource development. Sharia are the laws that govern the relationship between humans and creators and creatures. This study aims to determine how the Islamic perspective on human resource development. This study is a literature review using sharia as an approach, namely examining the problem with books and scientific works. The results of this study indicate that human resource development in the persective of sharia is a development in the form of training in skills, knowledge, behavior and sharia competence.